2018
DOI: 10.1177/0486613418788406
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting Bergmann’s Occupational Crowding Model

Abstract: In 1971, economist Barbara Bergmann developed the “occupational crowding model,” which posited that black men are “crowded into” low-wage occupations and “crowded out” of high-wage occupations due to employer discrimination. In quantitative analyses I have conducted for the years 2010 through 2011, the results have yielded a different picture from what Bergmann’s model predicts: although African American men are underrepresented in high-wage occupations, consistent with her model, this group does not appear to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 14 publications
(22 reference statements)
0
3
0
Order By: Relevance
“…Formal institutional barriers, discrimination by employers, and internalized biases can all contribute to occupational segregation. Racial and gender hierarchies can crowd subordinate group members into lower‐quality jobs in secondary labor markets and exclude them from primary sector opportunities where dominant group members are more represented (Bergmann, 1974; Gibson et al., 1998; Holder, 2018). According to Hamilton et al., 87% of occupations in the US are racially segregated which reinforces racial income gaps and inequality more broadly (Hamilton et al., 2011).…”
Section: Automation and Intersectionalitymentioning
confidence: 99%
“…Formal institutional barriers, discrimination by employers, and internalized biases can all contribute to occupational segregation. Racial and gender hierarchies can crowd subordinate group members into lower‐quality jobs in secondary labor markets and exclude them from primary sector opportunities where dominant group members are more represented (Bergmann, 1974; Gibson et al., 1998; Holder, 2018). According to Hamilton et al., 87% of occupations in the US are racially segregated which reinforces racial income gaps and inequality more broadly (Hamilton et al., 2011).…”
Section: Automation and Intersectionalitymentioning
confidence: 99%
“…(Du Bois 1962: 700) The "wage of whiteness" is both psychological and symbolic, as well as material, insofar as labor market racial inequality continues to crowd Black workers out of supervisory positions. Work on stratification economics and occupational crowding illustrate how-despite changes in the structure of the labor market over the course of the twentieth century-Black workers remain crowded out and underrepresented in high-status, high-pay work, including managerial positions (Holder 2018;Darity, Hamilton, and Stewart 2015;Hamilton and Darity 2012). This evidence suggests that labor discipline is not merely a means of solving contracting problems for capital, but also works to maintain racial hierarchies, intensifying and incentivizing divisions among the working class.…”
Section: Guard Labor and Racialized Labor Disciplinementioning
confidence: 99%
“…Although the concept of occupational crowding is more than five decades old (it was originally articulated on the heels of the Civil Rights Act of 1964), evidence shows that occupational crowding is still pervasive in the U.S. labor market. Researchers found that Black workers are underrepresented in certain high-paying occupations, such as management and professional occupations, despite having the degrees required to qualify for them (Hamilton, Austin, and Darity, 2011;Holder, 2018). That is, the number of predicted workers in an occupation given the degrees of workers and the number of observed workers in that occupation is skewed.…”
Section: Labor Market Discriminationmentioning
confidence: 99%